2018
DOI: 10.1039/c8ra03271h
|View full text |Cite
|
Sign up to set email alerts
|

Raw walnut shell modified by non-thermal plasma in ultrafine water mist for adsorptive removal of Cu(ii) from aqueous solution

Abstract: Non-thermal plasma in ultrafine water mist (UWM) is proposed to increase the content of COOH groups on the surface of raw walnut shell in order to improve its performance in the removal of Cu(II) from wastewater.The modified walnut shell surface was characterized by various techniques (BET, SEM-EDX and XPS), and it was observed that more COOH groups were generated. Oxygen disassociated from water mist by plasma bonded with the walnut shell to form activated sites of COOH groups. After Cu(II) adsorption, the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It must be noted that the pH was not adjusted within the mentioned study and it is not known, whether precipitation of the metal ions took place. Much lower adsorption capacity (i.e., 5.02 mg/g) of Cu(II) ions has been observed by Wu et al[69]. Adsorption capacity of raw walnut shells was enhanced to 39.4 mg/g by applying a method of non-thermal plasma in ultrafine water mist, which increased the content of carboxyl groups on the surface of walnut shells.…”
mentioning
confidence: 84%
“…It must be noted that the pH was not adjusted within the mentioned study and it is not known, whether precipitation of the metal ions took place. Much lower adsorption capacity (i.e., 5.02 mg/g) of Cu(II) ions has been observed by Wu et al[69]. Adsorption capacity of raw walnut shells was enhanced to 39.4 mg/g by applying a method of non-thermal plasma in ultrafine water mist, which increased the content of carboxyl groups on the surface of walnut shells.…”
mentioning
confidence: 84%
“…2 c) enlarged the pore size with many craters and cavities of various sizes, along with increased surface area. This was caused by remarkably energetic electrons and active free radicals attacking the external surface of RHs, thus, increasing the number of adsorption sites 63 . The porous structure is a significant factor for physical adsorption, for PFOA with large molecular weights could get into the developed inner pores of the RHs.…”
Section: Resultsmentioning
confidence: 99%
“…The BET surface area and SEM micrograph results of the plasma-treated PA-activated RHs samples also correspond to the adsorption efficiency, indicating that the appropriate use of DBD plasma to modify PA-activated RHs can effectively improve its PFOA adsorption capacity. Excess plasma treatment duration may have caused the plasma to break the structure of RHs, reducing the surface area for adsorption 63 . These results are in accordance with the iodine number values, where the highest iodine number was 945 mg/g obtained from the PA-activated RHs treated with plasma for 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…The reason could be that large number of the active particles in the plasma, including high-energy electrons, ions and neutral particles can bombard the surface of the biochar, and the local thermal effect caused by the streamer generated during discharge causes the atom to evaporate, causing some pits on the surface of the material. [40] Comparing the SEM images in c and e, it was found that the roughness of the surface of biochar increased as the treatment time increased. Compared with figures b and d, it was found that the plasma not only etched the surface of the biochar but also had a positive effect on clearing blocked channels.…”
Section: Surface Topographymentioning
confidence: 98%